Conceptual framework for the public administration of inclusive education - Tamm , Anatolyi (Theory and Practice of Public Administration, 2019)
The urgency of the problem is, first of all, related to the increasing number of such people in need. In its turn, it requires the establishment of a new approach to the state social policy towards people with disabilities. It also calls for crucial reforms in the existing educational system that would guarantee all people with disabilities equal access to all levels of educations throughout their lives. That is why, the need in the integrated mechanism of public administration that will ensure well coordinated, goal-oriented and effective management in the inclusive education is quite urgent. It also implies the topicality of the research. So, the search of the approaches to develop the inclusive education is an important issue. The development of such an effective system in Ukraine is possible based on the engagement of different factors, the most important of which is the increased financial aid to the educational system, the perfection of its legislative standards, relevant methodologies and staff competences. It is also considered necessary to create a positive civil opinion regarding inclusive education by means of calling in the media, organizing informational campaigns that would assist in implementation of laws for the people with disabilities to obtain education.